Antinociceptive Activity of Aqueous and Alcohol Extract of Evodia Rutaecarpa - Cai, Q. Y. (Medknow Publications & Media Pvt Ltd, 2014)
Water, methanol and ethanol extracts of Evodia rutaecarpa were tested for antinociceptive activity, which were correlated with the contents of evodiamine, rutaecarpine and evodine. Determination of contents was achieved by chromatographic techniques. Extracts were evaluated for antinociceptive activities using hot-plate test; acetic acid-induced writhing test and formalin test. All three extracts of Evodia rutaecarpa showed antinociceptive activities but the ethanol extract exhibited better effect. The better antinociceptive activity appeared to be related to higher contents of evodiamine, rutaecarpine and evodine in ethanol extract of Evodia rutaecarpa.